2018
DOI: 10.1002/joc.5926
|View full text |Cite
|
Sign up to set email alerts
|

Heavy rainfall events over southeast peninsular India during northeast monsoon: Role of El Niño and easterly wave activity

Abstract: The catastrophic floods over southeast peninsular India during 2015 northeast monsoon season (NEM, October-December) avowed 400 lives, affected more than 4 million people and reported a loss of property worth 3 billion US dollars. In the present study, an attempt has been made to understand the mechanism of occurrence of heavy rainfall events over southeast peninsular India during NEM, with a special emphasize on 2015 heavy rainfall events. In presence of strong El Niño, basin-wide warming and low-level easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Weaker northward propagation is noticed in SST and SSS only during these synoptic events (Figures 6c and 6d) and during monsoon withdrawal in SSS (Figure 6d). Previous studies have shown the 3-7-day ISO and LPS to have a wavelength of 2,000-3,000 km and a phase speed of about 7m/s (Goswami et al, 2003;Murakami, 1976;Sanap et al, 2019). This length scale is crucial, as it means that SMAP, that has a 1,000 km swath, is able to capture the structure of the 3-7-day mode.…”
Section: 1029/2020jc016200mentioning
confidence: 99%
“…Weaker northward propagation is noticed in SST and SSS only during these synoptic events (Figures 6c and 6d) and during monsoon withdrawal in SSS (Figure 6d). Previous studies have shown the 3-7-day ISO and LPS to have a wavelength of 2,000-3,000 km and a phase speed of about 7m/s (Goswami et al, 2003;Murakami, 1976;Sanap et al, 2019). This length scale is crucial, as it means that SMAP, that has a 1,000 km swath, is able to capture the structure of the 3-7-day mode.…”
Section: 1029/2020jc016200mentioning
confidence: 99%
“…The study of Rajeevan et al (2012) explained the association in the interannual variability of northeast monsoon over south peninsular India which is significantly linked with the phases and strengthening of ENSO and the Indian Ocean Dipole (IOD). Further, Sanap et al (2019) explained the occurrence of heavy rainfall during El Nino phase and is weaker during La Nina and neutral phase in northeast monsoon. In recent decades, relationship between ISMR and ENSO weakened (C. P. Chang et al, 2001;Kumar et al, 1999).…”
mentioning
confidence: 95%
“…Further, Sanap et al. (2019) explained the occurrence of heavy rainfall during El Nino phase and is weaker during La Nina and neutral phase in northeast monsoon. In recent decades, relationship between ISMR and ENSO weakened (C. P. Chang et al., 2001; Kumar et al.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, energy transfer that occurred at multiple time scales such as synoptic, quasi-biweekly, and intraseasonal phenomena might amplify the rainfall amount during the event (Krishnamurti et al 2017;Boyaj et al 2018). Previous studies focused on either case studies or particular seasons (Phadtare 2018;Boyaj et al 2018;Sanap et al 2019;Prathipati et al 2021). However, comprehensive studies of ERE over the SIP remain unexplored.…”
Section: Introductionmentioning
confidence: 99%